Market selection in global value chains - Philipp Mundt; Uwe Cantner; Hiroyasu Inoue; Ivan Savin; Simone Vannuccini (Bamberg University, Bamberg Economic Research Group (BERG), 2021)
The idea that market selection promotes survival and expansion of the 'fittest' producersis a key principle underlying theories of competition. Yet, despite its intuitive appeal, thehypothesis that companies with superior productivity also exhibit higher growth lacks em-pirical support. One reason for this is that companies are not 'islands' that produce goodsand services in isolation but depend on their suppliers in value chains, implying that exces-sive growth can also originate in the superior productive performance of these value-chainpartners. Neglecting these dependencies in empirical tests of the selection hypothesis leadsto measurement errors and may impair the identification of competition for the market.In this paper, we use data from the World Input-Output Database to capture these globalvalue-chain relationships in an empirical test for market selection, studying competitionbetween country-sectors for a global market share in different economic activities. Com-pared to the conventional view that focuses on individual productivities, our value-chainperspective on the productivity-growth nexus provides stronger empirical support for mar-ket selection. This suggests that the scope of selection reaches beyond the level of individualproducers and requires a systemic analysis of production networks. Our findings contributeto a better understanding of the determinants of selection in competitive environments andalso represent a novel application of global value-chain data.
Keywords: C67; D22; L14; L16; L20; 330; competition; country-sector dynamics; input-output analysis; replicator dynamics; productivity decomposition